Analisis Marketing Mix Terhadap Pembelian Properti Milik Pt. Beringin Subur Kencana - Felix Ananda Gunawan; M. Emil Rachman (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
The study's goal was to examine how factors like as pricing, promotion, product, and location influenced consumers' decisions to buy property held by PT Beringin Subur Kencana. Price, Product, Location, and Promotion were the four independent factors that were examined in the study. The participants in the study were those who had purchased PT Beringin Subur Kencana-owned property. There were 45 participants in the study as a whole. The entire population is taken because there are fewer than 100 people. Quantitative techniques are used in the analysis procedure. The price variable had the highest t value in this study, as a result. As a result, the most important factor in PT Beringin Subur Kencana's decision to buy property is pricing.